3D modelling of a 15th century city gate of Rennes: Portes Mordelaises - Jean-Baptiste Barreau; Elen Esnault; Jérôme Foucher; Manon Six; Cécile Le Faou (Virtual Archaeology Review)
The Portes Mordelaises, remnants of the medieval city walls of Rennes, France, has been the subject of several archaeological excavations until 2017. From these excavations, we created a three-dimensional (3D) model of the site reconstructed as it would have appeared during the 15th century, including the surrounding plus the interiors of its famed towers. Once our efforts and results were officially recognised as being of national interest by the French Ministry of Culture and Communication, Department of Heritage and the National Museum Service of France, we presented our virtual model reconstruction in an exhibition curated by the Museum of Bretagne, entitled "Rennes, les vies d'une ville" (Rennes, the Lives of a City). This approach to 3D reconstruction of the site served to further study Rennes’ origins, its construction, organisation, as well as its historic relationship to surrounding territories. The main objective of this work was to investigate, using of a significant and complex archaeological site as proof of concept, how the digitalisation of an existing structure, the modelling of its hypothetical structures, and the interactions with its virtual spaces enabled the general public to provide critical feedback, and enhance archaeological knowledge and evaluation of such sites. This reconstruction was carried out under a West Digital Conservatory of Archaeological Heritage project, whose mission is to support and advise archaeologists in the production and exploration of 3D archaeological datasets using the latest digitisation, modelling, and virtual reality (VR) techniques. Through a complex but repeatable process, using the valuable data provided by various excavations, in addition to new information provided by the 3D digitalisation itself, we produced a 3D model, fully satisfactory to rigorous scientific standards, which was then incorporated into a VR space ready for diffusion to the general public. Furthermore, the fact that 45850 visitors were welcome to experience our 3D model at an exhibition in a city the size of Rennes proved to be a significant success.